The effect of Public Debt on FDI-Growth Nexus: A Panel Analysis / Yong Sze Wei … [et.al.] - Yong, Sze Wei; Suhaimi, Rosita; Chai, Shin Yi (2017)
This paper aims to examine the linkages between Foreign Direct Investment and economic growth from public debt perspectives for five ASEAN countries, namely Indonesia, Malaysia, the Philippines, Singapore and Thailand over the period of 2000 to 2013. Precisely, this paper attempts to determine the long run relationship of FDI and economic growth and the impact of FDI on economic growth with the existence of public debt threshold effect via the panel analysis. The empirical result indicates that there is a positive and significant cointegrating relationship between FDI and economic growth for ASEAN-5 countries in long run. Furthermore, the result shows that the elasticity of GDP with respect to FDI is 0.526% by using the Fully Modified OLS (FMOLS) and 0.147% through the Dynamic OLS (DOLS) methods. Finally, our finding reveals that the impact of FDI on economic growth shows diminishing trends after public debt exceeds the pre-determined threshold level. This study provides new evidence to the policy makers and market investors on the role of public debt which bring the impact to the FDI and economic growth nexus. Thus, it is important for policy makers or government to emphasize on the different aspect such as public debt in formulating FDI policy in order to attract FDI inflow substantially to the host country.